Segregasi Sosial Pasca Pemilu 2019 dan Pentingnya Pendidikan Multikultural Islami - Nursyamsi, Pirman (Tsamratul Fikri | Jurnal Studi Islam, 2020)
The following research aims to describe the following matters: (1) Post 2019 Election Social Segregation in SMK Bakti Karya Parigi (2) The Importance of Multicultural Education in SMK Bakti Karya Parigi. The method used in this research is qualitative descriptive method. The data collection technique is by way of observation, interview, documentation study, and literature study. Furthermore, the research phase consists of pre-field stage, field stage and analysis phase and data interpretation. From the results of the study it was found that: (1) Post-2019 Social Segregation in the SMK Bakti Karya Parigi environment both in the school environment and in the dormitory environment has never happened, because all students, teachers and the local community tend to be accustomed to differences of opinion from any aspect, they seemed accustomed to the diversity and harmony that existed and seemed unconcerned by the heat of the country's democratic space that occurred after the 2019 elections, but they continued to work together in giving their voting rights in the 2019 elections. (2). SMK Bakti Karya Parigi as one of the pioneers of multicultural education in Indonesia has given a good example to the community to be able to respect and respect each other's differences so that people will not be easily provoked and manipulated by people who want to divide the unity and integrity of the people. Multicultural education for the community is very important because from the multicultural education the community will be able to understand differences, both in terms of religion, social, and culture.